Castelos de pixels: relacionamentos BDSM no mundo digital virtual 3D Second Life - Santos, Raíra Bohrer dos (2016)
Proceeding from ethnographic research conducted in digital virtual 3D Second Life world from 2013 to 2015, an analisys to identify and study the BDSM sociabilities as the relations of affection, love and sex among practitioners of this non-hegemonic kind of sexuality was carried. In this process, were observed issues such as sexual virtuality and body building for cibersexualities and the relationship between pain, humiliation and affection, love and gratitude in the hierarchical relationships of dominant and submissive participants of the BDSM communities encompassed in the online universe. Based on participant observation and interviews with virtual world SL residents, this work aims at understanding love relationships and negotiations that take place amidst sexual practices and morality values of the community. The relationships between practitioners draw a complex web of affections, enabling a micropolitics of emotions which is reflected in actions of care, gratitude and reciprocity. The notion of BDSM as a transgression, a sort of practice that, by being rationalized and controlled, in the search for its legitimacy, creates its own interdictions- such as romantic love and vanilla relationships- is also addressed.